Chemical Parameters Analysis of Diverse Casing Substrates Across Agaricus bisporus (Lange) Imbach Development under Natural Bamboo Hut Conditions - Manisha Saini; R. S. Jarial; Kumud Jarial (International Journal of Economic Plants)
The present study was conducted from September, 2019 to April, 2020 at College of Horticulture and Forestry, Neri, Hamirpur, Himachal Pradesh, India with an aim to examine the chemical parameters of various casing substrates and their changes throughout the crop development stages in Agaricus bisporus (Lange) Imbach production, under natural bamboo hut conditions. Chemical parameters of seven casing media viz., sawdust, spent compost (aged 2 years), coconut coir pith, farmyard manure (aged 2 years), vermicompost, and local soil were evaluated, amongst which, independent of the days after casing, local soil recorded the highest mean pH of 7.48, while the lowest mean pH of 6.17 was recorded in two-year-old spent compost. For electrical conductivity (EC), local soil recorded the highest mean value of 1150.04 µS and coconut coir pith recorded the lowest at 641.67 µS. In the commercial trial, irrespective of the days after casing, vermicompost-leached alone recorded the highest mean pH of 7.43, whereas the lowest mean pH of 6.30 was recorded in the control treatment (farmyard manure+local soil). Regarding EC, vermicompost-leached alone recorded the highest mean value of 1162.37 µS, while coconut coir pith recorded the lowest at 658.56 µS. Both pH and EC were tracked for up to 56 days after casing and the findings revealed that the pH of all casing substrates decreased as the crop progressed, while EC consistently increased over time.